The Place of Marriage in Natural Law: Defending Belonging as the Foundation of Husband and Wife Relationships - Silalahi, Ubat Pahala Charles; Alfasina, Muhammad Reza; Binsasi, Norbertus Antoine (MOZAIK HUMANIORA, 2024)
The relationship is an essential part of husband and wife. This bond between spouses is the basis of their intimacy. This study investigates the nature of the interrelationship in the institution of marriage. It highlights the concept of belonging as the foundational principle of marriage through a hermeneutical philosophical examination. The key findings of this article state that matrimony is an institutionalization between a man and a woman. The conjugal union is essentially natural and directed by moral virtues. Married partners formalize the activity through sacramental communion. Such integration entails a lifelong commitment to fidelity. Consequently, dissolution of this accord occurs due to the death of one of the spouses or the loss of the qualities that unite the couple. In addition, the sacrament of marriage serves as a representation of the couple’s presence before society. However, biological intimacy is an essential component of marriage. The sacrament of marriage, then, serves to prevent sexual pleasure beyond the binding of marriage. The principles of the nature and sacredness of marriage should guide sexual intimacy in the family. This research suggests that consensual non-monogamy is incompatible with the essence of marriage as it goes against the purpose and unity of the couples. The article emphasizes the importance of interpreting marriage as a divine relationship rooted in mutual belonging, moral excellence, and devotion.